Finite element simulation and experimental investigation of crystallographic orientation-dependent residual stress in diamond cutting of polycrystalline aluminum. (March 2023) - Qiu, Shi; Zhang, Chunyu; Zhao, Liang; Lu, Shijin; Li, Guo; Zhang, Junjie; Song, Chengwei; Zhang, Haijun
The residual stress of crystalline materials induced by deformation at grain level strongly correlates with crystal orientation. In the present work, the dependence of residual stress on crystallographic orientation in diamond cutting of polycrystalline aluminum is investigated by crystal plasticity finite element modeling and simulations. Furthermore, corresponding ultra-precision diamond cutting experiments, which have the same parameter setup with the finite element model, are also carried out. The crystallographic orientations of the specimens are depicted by electron back-scattered diffraction characterization, and the surface residual stress is measured by X-ray diffraction. Both experiment and finite element simulation results demonstrate the anisotropic characteristics of the residual stress within machined polycrystalline aluminum, which exhibits the significant correlation with crystallographic orientation. Furthermore, finite element simulations of bi-crystal cutting are also performed, which indicate that the grain boundary also has a strong influence on the generation of residual stress.